AB0189 Macrophages polarization in the gut of patients with ankylosing spondylitis. (23rd January 2014) - Ciccia, F.; Alessandro, R.; Rizzo, A.; Accardo-Palumbo, A.; Guggino, G.; Giardina, A.; Triolo, G.
Abstract : Background: Subclinical gut inflammation occurs in patients with Ankylosing Spondylitis (AS) and long term evolution to overt Crohn's disease (CD) has been described in these patients. Gut mucosal macrophages represent the largest pool of tissue macrophages in the body. Different pathways of macrophage activation have been described in humans. Objectives: To study the macrophages polarization occurring in the inflamed gut of AS patients. Methods: Twenty two consecutive HLA-B27 + Ankylosing Spondylitis (AS) patients, 15 Crohn's Disease (CD) patients and 15 normal controls were included in this study. Four AS patients developed an overt CD during the follow-up and were included. Ileal macrophage subsets were characterized by immunohistochemistry and flow cytometry. Quantitative gene expression analysis, by Real Time-PCR of IFN-g, IRF5, IL-4, IL-5, IL-33 and STAT6 was also performed. Results: CD68 + macrophages were expanded in both AS and CD patients but not in controls. Inducible nitric synthase (iNOS + ) macrophages were increased in both AS and CD patients and comprised classical M1 macrophages (iNOS + IL-10 - ) and resolution phase macrophages (rMs) (iNOS + IL-10 + ). Adaptive immunity, valued through IFN-g expression, was the main M1-polarizing factor in CD whereas innate immune M1 response, valued through IRF-5 induction, predominates in AS. Increased numbers of CD163 + (M2) macrophages were observed in both AS and CD patients together with increased expression of Th2 cytokines and the Th2 transcription factor STAT6. Unlike in CD, CD14 + macrophages were virtually absent in the gut of AS patients and controls. On the other hand CD14 + macrophages were observed to be expanded in the four AS patients that developed CD. Conclusions: M1, M2 macrophages and rMs expansion was observed in both AS and CD. IL-33 over-expression immunologically characterizes AS gut inflammation. CD14 + macrophages were observed in CD patients and appear to characterize evolution from subclinical towards clinically evident gut inflammation in AS. Disclosure of Interest: None Declared